Master-class: from a bibliographic lists to mapping its content (evidently for modeling an exhibition) - V. A. Borodina (Библиосфера)
An innovative component of modern library-information education should become a trend, in which frames it is possible not only to compact and intensify the study of professional issues, but also to shape tools for future professional activities in the innovation logic of an effective character. This in turn requires integrating multiple types of work in a holistic format. A master class on modeling personal exhibitions and its results in developing problems of reading study with application of bibliographic reconstruction and knowledge mapping is chosen as one of these formats. In the master class course a complex of tasks was solved. Among them are the following: developing the strategy of exhibition modeling, its understanding according to the completeness of information and its degree of semantic coagulation as a way to learn and present information in the exhibition format; forming the communicative culture in the exhibition presentation process; improving analytical skills, creative thinking, and improvement of psychologic-pedagogical professionalism through familiarization with the personal contribution of a scientist related to readers study; the acquisition of knowledge and skills to map knowledge. The exhibition was carried out in several stages in the logic «from simple to complex» and starts with learning the exhibition structural design options, their semantic and color solutions; exploring the scientist contribution based on the bibliographic description of publications, annotations and abstracts, later on the basis of studying publications themselves and citation. The latter allows not only to map its content in different ways, but also to build the professional communication sociometric matrix. As a result of this master class with elements of a business game students acquire specific knowledge (in our case readers’ study); a various options of a personal exhibition intelligent-information products are created; the specialist intellectual capacity grows significantly, cognitive and metacognitive skills of specialists are developed; methodological knowledge based on innovative search activities is formed. The heuristic potential of the master class lies in the fact that the tendency to internal resources of a personality determining the propensity to innovate in their professional activities is clearly expressed in the world and domestic science.